Unitary colligations and parametrization formulas - Arocena, R. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The aim of this paper is to describe, in a rather concise but relatively self-contained manner, some relations between unitary colligations which are regarded as linear systems, and parametrization formulas for the solutions of some interpolation problems.